2015
DOI: 10.1097/cnd.0000000000000098
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic Findings in 5 Patients With Hypomyopathic Dermatomyositis

Abstract: Muscle histopathologic findings in hypomyopathic dermatomyositis (HDM) have not been adequately characterized. We sought to determine the results of conventional and immunohistopathology in HDM. Light microscopic and immunohistochemical analysis was performed on muscle from 5 patients with HDM without muscle weakness. Ages ranged from 49 to 56 years. Creatine kinase level was normal. Electromyography showed mild "myopathic" changes in 2. The median duration of skin disease before biopsy was 18 months. Abnormal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Therefore MHC-I is considered as an effective molecular marker for PM. The increased level of MHC-I molecule in the skeletal muscle is associated with muscle fiber damage and/or induction of endoplasmic reticulum stress, contributing to muscle dysfunction [ 27 , 28 ]. Moreover, a previous study showed that the overexpression of MHC-I alone in the mice skeletal muscle could lead to a self-sustaining inflammatory process involving muscle fiber damage and infiltration of mononuclear cells with the most of the characteristic features of human PM, and suggested that the up-regulation of MHC-I may initiate a cascade of events typical of muscle inflammation in the spontaneous human disease [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore MHC-I is considered as an effective molecular marker for PM. The increased level of MHC-I molecule in the skeletal muscle is associated with muscle fiber damage and/or induction of endoplasmic reticulum stress, contributing to muscle dysfunction [ 27 , 28 ]. Moreover, a previous study showed that the overexpression of MHC-I alone in the mice skeletal muscle could lead to a self-sustaining inflammatory process involving muscle fiber damage and infiltration of mononuclear cells with the most of the characteristic features of human PM, and suggested that the up-regulation of MHC-I may initiate a cascade of events typical of muscle inflammation in the spontaneous human disease [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…An atypical form of dermatomyositis is hypomyopathic dermatomyositis. Clinically amyopathic dermatomyositis (CADM) accounts for approximately 20% of dermatomyositis, which includes amyopathic dermatomyositis (ADM) and hypomyopathic dermatomyositis (HDM) 1,2 . The former refers to characteristic cutaneous manifestations without evidence of myopathy for two or more years.…”
Section: Introductionmentioning
confidence: 99%
“…Combinatorial regulation of PD-L1 and MHC-1 expression with both CRISPR-Cas9 and CRISPR-dCas9 systems could be an effective strategy to remodel tumor immunogenicity for efficient cancer immunotherapy. However, PD-L1 and MHC-1 are also expressed in immune cells and normal tissues, , which may raise safety concerns after the systemic administration of CRISPR agents. Besides, the intrinsic mechanism of the CRISPR system requires that it must overcome multiple physiological barriers to enter targeted cells .…”
mentioning
confidence: 99%